Uji validitas dan praktikalitas modul fisika mengintegrasikan pembelajaran kontekstual dan literasi lingkungan materi gelombang mekanik untuk siswa kelas XI SMA - Khairunnisa Khairunnisa; Asrizal Asrizal; Desnita Desnita; Yenni Darvina (Universitas Negeri Padang, 2020)
21st Century learning requires a variety of skills that must be mastered by students. This 21st Century requires students to have 4C skills, namely: critical thinking, creative, collaborative and communicative. In addition, the 21st Century requires students to have the ability to explain phenomena in everyday life. The purpose of this study was to determine the validity and practicality of the physics module by integrating contextual learning and environmental literacy. The type of research was Research and Development (R&D). The object of this research was physics module integrate contextual learning and environmental literacy in a limited trial to one of the XI classes of SMAN 7 Padang. The data source of this research was experts who include Physics lecturers at the Faculty of Mathematics and Natural Sciences UNP as validators, physics teachers at SMAN 7 Padang practitioners, with class XI MIA 3 students as physics module users. Data collection instruments used in the study were : validity sheets, practicality test sheets, data analysis techniques used were descriptive analysis of product validity and product practicality. Based on data analysis from the research that has been done can be presented three research results. First, the validation of the physics module integrate contextual learning and environmental literacy with an average value of 85.12 which was excellent category. Second, the practical physics module integrates contextual learning and environmental literacy with an average value by teacher was 91.33 and practicality by students was 93.73 according to the category of practice very good.